2004
DOI: 10.1002/pros.20135
|View full text |Cite
|
Sign up to set email alerts
|

Induction of PSA‐specific CTLs and anti‐tumor immunity by a genetic prostate cancer vaccine

Abstract: We demonstrate that immunization with a PSA DNA vaccine can evoke PSA-specific cellular immune responses. We also show, for the first time, that a PSA DNA vaccine can induce anti-tumor immunity in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…The potential of PSA as an antigen in immunotherapy is due to its overexpression in malignant prostate cells and low expression by normal prostate epithelial cells and other organs, such as the small intestine and testes (3). There is a great deal of information regarding the potential of this antigen for the treatment of prostate cancer (1,10,15,17,25). Previously, we showed that a recombinant L. monocytogenes vaccine expressing PSA (Lm-LLO-PSA) can cause the regression of solid tumors expressing PSA in a murine model for prostate cancer (27).…”
mentioning
confidence: 99%
“…The potential of PSA as an antigen in immunotherapy is due to its overexpression in malignant prostate cells and low expression by normal prostate epithelial cells and other organs, such as the small intestine and testes (3). There is a great deal of information regarding the potential of this antigen for the treatment of prostate cancer (1,10,15,17,25). Previously, we showed that a recombinant L. monocytogenes vaccine expressing PSA (Lm-LLO-PSA) can cause the regression of solid tumors expressing PSA in a murine model for prostate cancer (27).…”
mentioning
confidence: 99%
“…Other examples include treatment with defined peptide antigens like PSA (34), carbohydrate antigens (35), vaccinia vectors expressing PSA (36), and infusions of GM-CSF-activated autologous dendritic cells loaded ex vivo with defined prostate-specific peptides, such as prostate-specific membrane antigen and prostatic acid phosphatase (37,38), or even amplified prostate tumor RNA (39). New tumor-associated antigens and antibodies discovered in this and other immunotherapy trials could themselves become candidate therapeutic molecules using recombinant DNA technologies.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that a DNA vaccine encoding PSA induces Ag-specific Ab and cellular immunity, in particular CTL in mice (Kim et al, 1998b). Further co-injection of PSA DNA vaccines with DNA expressing IL-2 and GM-CSF induced a significant level of Ag-specific CTL and antitumor responses to PSA-expressing tumors (Roos et al, 2005). More recently, ID-EP has been demonstrated to be a more effective way to induce PSA-specific immune responses (Roos et al, 2006).…”
Section: Prostate Cancermentioning
confidence: 99%